Hydrogen production from sodium borohydride: the role of Ni-Ru supported catalysts - Nunes, H. X. (2020)
ABSTRACT: Nowadays, the concerns about greenhouse-gas emissions from fossil fuel sources are generating a demand for clean and abundant energy. Since early 2000’s the chemical hydrides, in particular sodium borohydride (NaBH4), hydrolysis reaction attracted much attention as a hydrogen carrier due to its high hydrogen storage capacity, safe handling and fast kinetics of hydrogen release. Although, during the last decades, several studies have been focused on sodium borohydride hydrolysis improvement, the reaction kinetics is not fully understood. Thus, the performance of nickel-ruthenium supported catalysts was studied both in alkaline hydrolysis (x = 16) and alkali-free hydrolysis (x = 2) reactions. The results present high hydrogen generation rates, at uncontrolled room temperature, that compete directly with the rates previously obtained with a nickel-ruthenium unsupported catalyst, which are advantages for an on demand low/medium power NaBH4-H2-PEMFC system.